The Effect of Compensation and Training on Work Performance that Has an Impact on Employee Performance - Dede Andi (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2022)
This study aims to determine the effect of compensation and training on work performance which has an impact on employee performance at PT Cahaya Pratama Mandiri in Cilegon Banten. The method used is explanatory research with a sample of 100 respondents. The analysis technique uses statistical analysis with regression, correlation, determination, and hypothesis testing. The results of this study Compensation has a significant effect on work performance by 36.4%, hypothesis testing obtained a significance of 0.000 <0.05. Training has a significant effect on job performance by 46.3%, hypothesis testing obtained a significance of 0.000 <0.05. Simultaneous compensation and training have a significant effect on work performance by 52.9%, hypothesis testing obtained a significance of 0.000 <0.05. Work achievement has a significant effect on employee performance by 31.0%, hypothesis testing obtained a significance of 0.000 <0.05.